A PILOT STUDY ON INTEGRATING COGNITIVE BEHAVIOURAL THERAPY AND BIOFEEDBACK IN COUNSELLING JUVENILE CLIENTS AT A MALAYSIAN REHABILITATION CENTRE - Saidi, Liley Afzani; Abdul Wahab, Muhammad Nubli (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This pilot study, conducted in a Malaysian juvenile rehabilitation institution, explored the implementation and effectiveness of a structured counselling protocol that integrates Cognitive Behavioural Therapy (CBT) with Heart Rate Variability (HRV) biofeedback to address emotional deregulation and behavioural difficulties among adolescents with traumatic backgrounds, impulsivity, and poor self-regulation. Using a qualitative case study design, ten male adolescents aged 14 to 17 participated in eight structured sessions involving CBT techniques such as the ABC model, cognitive restructuring, visualization, and imagery descripting, combined with HRV biofeedback to support real-time physiological regulation. Data were collected through observation, session notes, client journals, and HRV recordings. Thematic analysis revealed significant outcomes including increased emotional awareness, improved engagement, reduced impulsivity, and enhanced self-efficacy. Participants showed progress in linking thoughts to emotional and physiological responses and began applying coping strategies in real-life situations. The biofeedback component notably increased motivation and insight, especially among those initially resistant to traditional talk therapy. Overall, the integrated CBT-biofeedback approach promoted greater autonomy in emotional and behavioural regulation, demonstrating its clinical potential as a holistic and sustainable therapeutic model for high-risk adolescent populations in rehabilitation settings.